A novel Ti42.5Zr42.5Nb5Ta10 multi-principal element alloy with excellent properties for biomedical applications. (December 2022) - Li, Zheng; Lai, Weiji; Wang, Binbin; Tong, Xin; You, Deqiang; Li, Wei; Wang, Xiaojian
Abstract: Body-centered cubic (BCC) Ti–Zr–Nb–Ta multi-principal element alloys (MPEAs) have drawn extensive research attention as orthopedic implant materials. In this work, a novel Ti42.5 Zr42.5 Nb5 Ta10 multi-principal element alloy was developed for biomedical applications in terms of its microstructure, mechanical properties, wear performance, corrosion behavior, and in vitro biocompatibility. The Ti42.5 Zr42.5 Nb5 Ta10 alloy after cold rolling followed by annealing at 880 °C (TZNT-880), possessed excellent mechanical properties combination, with a yield strength of 839.5 MPa, elongation at fracture of 22.6%, and Young's modulus of 63.2 GPa, superior to most of the currently existing biomedical BCC MPEAs. Meanwhile, TZNT-880 alloy exhibited higher wear resistance compared with commercial CP-Ti and Ti6Al4V, which is strongly related to its high H/E and H 3 /E 2 values. Also, TZNT-880 alloy showed good corrosion resistance, as revealed by a nobler corrosion potential, lower corrosion current densities, and higher passivation stability, which is attributed to the formation of passivation films consisting of TiO2, ZrO2, Nb2 O5, and Ta2 O5 . The in vitro biocompatibility tests demonstrated that the TiZrNbTa alloys can support cell adhesion and proliferation with high biocompatibility comparable to that of CP-Ti and Ti6Al4V, indicating their potential as a candidate for implant material. Highlights: A novel Ti42.5 Zr42.5 Nb5 Ta10 multi-principal element alloy was developed for biomedical applications. After cold rolling followed by annealing at 880 °C, TZNT-880 exhibited a good modulus-strength-ductility combination. The TZNT-880 alloy exhibited high wear, corrosion resistance, and biocompatibility compared to those of CP-Ti and Ti6Al4V. The high strength of Ti42.5 Zr42.5 Nb5 Ta10 alloy is dominantly attributed to the solid-solution strengthening effect.